How Cr2O3 influences the microstructure and nonohmic features of the SnO2(COx, Mn1-x)O-based varistor system - Bacelar, W. K.; Bueno, Paulo Roberto [UNESP]; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2006)
An investigation was made to discover how the addition of Cr2O3 affects the microstructural heterogeneity and nonohmic features of the SnO2(Co-x, Mn1-x)O-based varistor system, with x varying from 0 to 1. The presence of Cr2O3 was found to strongly increase the nonohmic features when x = 1. However, the nonohmic features of the system decrease when x drops from 1 to 0, a behavior explained by the increase of the junction heterogeneity within the system's microstructure. accompanied by ail excess of precipitates at the triple point in the grain boundary region due to modified MnO sintering. The presence of these precipitates causes the leakage current to increase in response to the creation of ail ineffective barrier. The effect produced by heat-treating these systems in oxygen- and nitrogen-rich atmospheres suggests that, according to mechanisms previously discussed in the literature, Cr2O3 is more susceptible to oxygen, so that increasing the amount of oxygen in the grain boundary region may improve the system's nonohmic properties. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: varistor; Cr2O3; SnO2; microstructure-final